Retrospective cohort analysis of survival of children living with HIV/AIDS in Mumbai, India - Shrikala Acharya; Amol Palkar; Anwar Parvez Sayed; Maninder Singh Setia (BMJ Open)
Objectives To understand the survival in a cohort of children living with HIV/AIDS (CLHAs) and to study the factors associated with survival in CLHAs in government antiretroviral therapy (ART) centres in Mumbai, India.Design This is a retrospective cohort analysis.Setting Data from electronic ART records of children from 15 ART centres in Mumbai, Maharashtra, India.Participants 2224 CLHAs registered in one of these ART centres from 2004 until October 2019. CLHAs up to the age of 18 at the time of registration were considered for these analyses.Primary and secondary outcomes We accessed the following data: date of test, date of initiation of ART, date of last follow-up, age at the time of registration, gender, potential route of infection, baseline CD4 counts, ART regimen, adherence and presence of co-infection (TB). We estimated the survival probabilities, plotted the Kaplan-Meier survival graphs and estimated HRs for mortality.Results The mortality rate in our population was 22.75 (95% CI 20.02 to 25.85) per 1000 person-years. The 1-year survival was 0.92 (95% CI 0.91 to 0.93), 0.89 (95% CI 0.88 to 0.91) at 5 years and 0.85 (95% CI 0.83 to 0.87) at 10 years after initiation of ART. Children with adherence less than 80% had lowest survival in the first year (0.54, 95% CI 0.46 to 0.61). It reduced drastically at 5 and 10 years. After adjusting for demographic and clinical parameters, mortality was associated with poor adherence (<80%) (HR 11.70, 95% CI 8.82 to 15.53; p<0.001). However, CD4 counts of greater than 200 and age more than 1 year were protective.Conclusions Poor adherence to ART and low CD4 counts were significantly associated with higher mortality. Adherence counselling should be an important component of CLHA monitoring in all ART centres. It is also important to identify children early in the infection and start ART medications appropriately.